A second look at the agricultural land reform code of 1963 - Guevara, Sulpicio (1964)
The Agricultural Land Reform Code of 1963 has lately superseded the Land Reform Act of 1955, otherwise known as the Republic Act No. 1400. although the Code is intended to ameliorate the lot of the Filipino tenant and farmer, it has nevertheless elicited divergent reactions from many sides. Some of these reactions are interpretative of the sociological implications of the new code, others of its political consequences, and still many consider its possible economic repercussions. The following article by a professsor of law might well be termed "a legal reaction".
Includes bibliographical references.